Job separation and sick leave in the long-term care sector in England - Florin Vadean; Eirini Saloniki (Global Labor Organization (GLO), 2021)
Staff turnover in the long-term care (LTC) sector in England is perceived to be relatively high. Most job leavers do not leave the sector, but rather move to other LTC employers. Nevertheless, there are concerns that the high 'churn' has a negative impact on continuity and quality of care, care providers' recruitment and training costs, and the remaining staff workload and motivation. Using a large employer-employee panel dataset, this study aimed to provide quantitative evidence on the drivers of LTC staff retention and sick leave in England, with a focus on job quality. After controlling for observed individual, organisational and local market characteristics as well as unobserved worker and employer heterogeneity, we found that, everything else being equal, wages and employment conditions (i.e. full time contracts and contracts with guaranteed working hours) significantly improve staff retention. The wage effect was significantly underestimated when not controlling for unobserved heterogeneity. Our findings show that improving pay and employment conditions for care staff employed by independent providers would reduce the staff turnover in LTC. We also found that, everything else being equal, the amount of sick leave was strongly associated with employment in publicly owned care establishments, most likely due to the relatively more generous sick leave terms they offer.
Keywords: C23; J31; J63; J81; 330; job separation; long-term care; job quality; sick leave; England